PENGARUH SUBSTITUSI TEPUNG AMPAS TAHU TERHADAP KUALITAS KULIT PIE - Vitaloka, Yola; Faridah, Anni; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was based on the utilization of dregs of waste tofu in the processing of food is still small. Flour dregs know to have high protein nutritional value. This study aims to analyze the effect of soybean meal substitution of 20%, 40%, and 60% on the quality of shapes, color, aroma, texture and taste of pie skin. The best quality results on X2 (40%), best quality of color on X1 (20%), best scent quality at X2 (40%), best quality texture on X2 (40%) and best taste quality on X1 (20%). This study was a pure experiment with a complete randomized design method of three repetitions. The instrument used is a questionnaire which is then analyzed by organoleptic test. The data that have been obtained is tabulated and analyzed by variant (ANAVA). If different proceed with Duncan test. Based on the result of research indicate that overall the best value is found in the substitution of dregs of tofu waste as much as 40% (X2).Keywords: Flour dregs tofu, Leather pie, Quality